glass cloth

CN122980092APending Publication Date: 2026-10-27SHIN ETSU CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610536688.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-24
Filing Date
2026-04-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是,利用该方法也没有解决玻璃布的断裂、开线等问题

Benefits of technology

可提供具有优异的介电特性、断裂少、量产性优异的玻璃布。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

To solve the problem, the present invention provides a glass cloth having excellent dielectric properties, few breaks, and excellent mass productivity. The glass cloth is characterized in that it is a glass cloth composed of glass filaments as warp and weft, the warp is composed of warp (1) and warp (2), the warp (1) and warp (2) are two kinds of glass filaments having different SiO2 contents, the warp (2) constitutes at least one edge portion of both edge portions in the width direction of the glass cloth, the edge portion woven with the warp (2) has the entire edge portion attached with organic resin, the width T1 woven with the warp (2) and the width R1 attached with organic resin satisfy T1 / R1≤1, and the weft is a glass filament having a SiO2 content of 90% by mass or more. Warp (1): a glass filament having a SiO2 content of 90% by mass or more, warp (2): a glass filament having a SiO2 content of 50% by mass or more and less than 90% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to glass cloth. Background Technology

[0002] Today, with the increasing performance and high-speed communication of information terminals such as smartphones, printed circuit boards (PCBs) require not only high density and ultra-thinness but also lower dielectric properties. This necessitates lower dielectric loss tangents for the glass cloth used as the insulating material in these PCBs. For example, as described in Patent Document 1, a glass cloth with improved dielectric properties has been proposed. Furthermore, Patent Document 2 proposes a quartz glass cloth with a very low dielectric loss tangent due to its high SiO2 content.

[0003] Glass cloth composed solely of glass fibers with a SiO2 content of 90% or more has a very low dielectric loss tangent, but it is harder and more brittle than glass of other compositions. Therefore, there is a problem of glass cloth breaking during winding.

[0004] As a countermeasure, one method involves coating the two edges of the glass cloth in the width direction with organic resin to apply a reinforcing section known as a selvage. However, this method has not solved problems such as breakage and thread breakage in the glass cloth.

[0005] The breakage of glass cloth can also affect the yield rate when manufacturing printed circuit boards, so solutions to this problem are sought.

[0006] Existing technical documents Patent documents Patent Document 1: International Publication No. 2021 / 205698 Patent document 2: Japanese Patent Application Publication No. 2021-195689. Summary of the Invention

[0007] The problem the invention aims to solve Against the background described above, the object of the present invention is to provide a glass cloth with excellent dielectric properties, low breakage, and excellent mass production capability.

[0008] Methods for solving problems In order to achieve the above-mentioned objective, the inventors conducted in-depth research and found that the fracture started from the two edges of the glass cloth in the width direction, especially the part with organic resin attached.

[0009] It was discovered that by using the following glass cloth, breakage from the edge can be reduced, and a glass cloth with excellent mass production properties can be obtained, thus completing the present invention. The glass cloth is a glass cloth made of glass fibers as warp and weft yarns. The aforementioned warp yarns are composed of two types of glass fibers: warp yarn (1) [glass fibers with a SiO2 composition of 90% or more by mass] and warp yarn (2) [glass fibers with a SiO2 composition of 50% or more by mass and less than 90% by mass]. The aforementioned weft yarns are composed of glass fibers with a SiO2 composition of 90% or more by mass. The aforementioned warp yarn (2) constitutes at least one of the two edge portions in the width direction of the glass cloth. All edge portions woven from the aforementioned warp yarn (2) are coated with organic resin, and the width T1 woven from the aforementioned warp yarn (2) and the width R1 coated with organic resin are within a specified range.

[0010] Therefore, the present invention provides the following glass cloth.

[0011] [1] Glass cloth, characterized in that it is a glass cloth made of glass fibers as warp and weft yarns, wherein the aforementioned warp yarns are composed of the following warp yarns (1) and warp yarns (2), wherein the warp yarns (1) and warp yarns (2) are two kinds of glass fibers with different SiO2 composition, wherein the aforementioned warp yarns (2) constitute at least one of the two edge portions in the width direction of the glass cloth, wherein all edge portions woven by the aforementioned warp yarns (2) are attached with organic resin, and wherein the width T1 woven by the aforementioned warp yarns (2) and the width R1 attached with organic resin are T1 / R1≤1, and wherein the aforementioned weft yarns are glass fibers with a SiO2 composition of 90% by mass or more.

[0012] Warp yarn (1): Glass fiber with a SiO2 content of 90% or more by mass. Warp yarn (2): Glass fiber with a SiO2 content of more than 50% by mass and less than 90% by mass.

[0013] [2] The glass cloth according to [1] is characterized in that the glass cloth is a glass cloth that has been surface treated with a silane coupling agent, and the portion not attached with the aforementioned organic resin has a dielectric loss tangent of less than 0.0008 at 10 GHz.

[0014] Invention Effects We can provide glass cloth with excellent dielectric properties, low breakage, and excellent mass production capabilities. Attached Figure Description

[0015] Figure 1 This is a schematic diagram illustrating the glass cloth of the present invention.

[0016] Figure 2 This is a schematic diagram illustrating the glass cloth of the present invention. Detailed Implementation

[0017] The present invention will now be described in detail.

[0018] [Glass cloth] The glass cloth of the present invention is constructed using glass fibers as warp and weft yarns. It is characterized in that the warp yarns of the glass cloth are composed of the following warp yarns (1) and warp yarns (2), wherein the warp yarns (1) and warp yarns (2) are two types of glass fibers with different SiO2 compositions, and the aforementioned warp yarns (2) constitute at least one of the two edge portions in the width direction of the glass cloth.

[0019] The warp yarn (1) is a glass fiber with a SiO2 content of 90% or more by mass, and the warp yarn (2) is a glass fiber with a SiO2 content of 50% or more but less than 90% by mass.

[0020] The aforementioned warp yarns (2) constitute at least one of the two edge portions in the width direction of the glass cloth. From the viewpoint of suppressing breakage from the two edge portions, it is preferable that the aforementioned warp yarns (2) constitute both edge portions in the width direction of the glass cloth. Furthermore, all edge portions woven from the aforementioned warp yarns (2) are coated with organic resin to prevent unraveling. From the viewpoint of reducing the dielectric loss tangent of the glass cloth, the width T1 of the edge portion woven from the warp yarns (2) and the coating width R1 of the organic resin are T1 / R1≤1, preferably 0.2≤T1 / R1≤1.

[0021] The width of T1 is preferably 0.1 mm or more, and more preferably 0.5 to 10.0 mm.

[0022] The relationship between the width T1 of the edge woven from the warp yarn (2) and the adhesion width R1 of the organic resin will be explained below using the accompanying drawings. It should be noted that the present invention is not limited to the accompanying drawings.

[0023] Figure 1 The glass cloth 10 is shown schematically as one embodiment of the glass cloth of the present invention. Figure 1 And later Figure 2 This diagram shows the glass cloth as viewed from above. The glass cloth 10 has a region 11 woven from warp yarns (1) (including the central portion of the glass cloth 10), and regions 12 woven from warp yarns (2) (the two edges of the glass cloth 10) are located on the outer sides (both ends) of the width direction of the region 11. The regions 12 woven from warp yarns (2) constitute the two edges of the glass cloth 10. The width of each of the two edges woven from warp yarns (2) is denoted by T1. It should be noted that... Figure 1The diagram shows a glass cloth with two edges made of warp yarns (2), but it is also possible for a glass cloth to have only one edge made of warp yarns (2). In other words, the other edge may not be made of warp yarns (2), that is, the width T1 can be 0, in which case T1 / R1 of the other edge becomes 0.

[0024] 10 preferred glass cloth Figure 2 As shown, organic resin is attached to the region 13, including the entirety of the two edge portions 12 woven from the warp yarns (2). Figure 2 In the process, organic resin is attached to region 12 (both edges) and a portion of region 11 of glass cloth 10, and the attachment width of the organic resin is represented by R1.

[0025] As described above, the width T1 of the edge and the adhesion width R1 of the organic resin are T1 / R1≤1, preferably 0.2≤T1 / R1≤1.

[0026] It should be noted that, in Figure 1 , 2 In the diagram, the width T1 of both sides (left and right ends in the figure) of the glass cloth 10 is represented by the same length, but it can be of different lengths. Additionally, in... Figure 2 In the figure, the same length is used to represent the adhesion width R1 of the organic resin on both sides (left end and right end of the figure) in the width direction of the glass cloth 10, but it can be different lengths.

[0027] When the width T1 on both sides of the glass cloth 10 is of different length or the width R1 on both sides is of different length, the T1 / R1 on both sides can be different values. In this case, the T1 / R1 on both sides must satisfy T1 / R1≤1, preferably the T1 / R1 on both sides must satisfy 0.2≤T1 / R1≤1.

[0028] The aforementioned organic resins are not particularly limited, and examples include thermosetting resins and UV-curing resins. More specifically, examples include epoxy resins, ester resins, polyether polymers, amide resins, urethane resins, and acrylic resins. Among these, epoxy resins and ester resins are preferred.

[0029] The two edges woven from the aforementioned warp yarns (2) and coated with organic resin are usually referred to as "seams" in glass cloth. The seams can be partially or entirely cut off for use, or they can be left entirely without cutting them off. To prevent the threads from coming undone, it is preferable to cut off a portion of them.

[0030] Furthermore, the glass cloth of the present invention is characterized in that all weft yarns are glass fibers with a SiO2 content of 90% or more by mass. This facilitates the reduction of the dielectric loss tangent.

[0031] There are no particular limitations on the weave structure of glass cloth; examples include plain weave, twill weave, satin weave, and square weave. Among these, plain weave is preferred.

[0032] There is no specific limit to the weight per unit area of ​​fiberglass cloth; 10~100g / m² is suitable. 2 Fiberglass cloth.

[0033] Regarding the dielectric loss tangent of the glass cloth at 10 GHz, the portion of the glass cloth that has undergone surface treatment with a silane coupling agent and is free of organic resin is preferably 0.0008 or less, more preferably 0.0001 to 0.0005. Within this range, glass cloth with excellent dielectric properties can be easily obtained. Furthermore, the portion of the glass cloth free of organic resin is preferably a portion where the SiO2 content of both the warp and weft yarns is 90% by mass or more, more preferably a portion where the SiO2 content of both the warp and weft yarns is 95% by mass or more, and even more preferably a portion where the SiO2 content of both the warp and weft yarns is 99% by mass or more.

[0034] In this invention, the dielectric loss tangent is measured using a cavity resonator.

[0035] [Glass fiber] The glass fiber used in the manufacture of the glass cloth of the present invention can be quartz glass in which the SiO2 content in the total amount of warp (1) and weft yarn is 90% or more by mass.

[0036] From the viewpoint of dielectric properties, the warp (1) and weft yarns are preferably glass fibers with a SiO2 content of 95% by mass or more, and more preferably glass fibers with a SiO2 content of 99% by mass or more. It should be noted that the SiO2 content of the warp (1) and weft yarns can be the same or different.

[0037] The warp yarn (2) is not particularly limited as long as it is a glass fiber with a SiO2 content of 50% or more and less than 90% by mass. Examples include E glass with a SiO2 content of 53% by mass, S glass with a SiO2 content of 64% by mass, T glass with a SiO2 content of 65% by mass, and D glass with a SiO2 content of 72% by mass.

[0038] The SiO2 content of the warp yarn (2) is preferably 50% by mass or more and 85% by mass or less, more preferably 50% by mass or more and 80% by mass or less.

[0039] The thickness of the glass filaments used in this invention is preferably 0.5 g / km to 30 g / km in terms of count, and more preferably 0.8 g / km to 20 g / km. In addition, in order to stabilize the winding state, the count of the glass filaments in the warp yarn (2) is preferably equal to or less than the count of the glass filaments in the warp yarn (1).

[0040] [Method for manufacturing glass cloth] As for the manufacturing method of the glass cloth of the present invention, there is no particular limitation as long as it includes the process of weaving glass fibers, and methods including the following processes can be listed as examples. (1) The warping process of obtaining a bundle by warping glass wire; (2) The weaving process of weaving glass fibers to obtain glass cloth; (3) Degreasing process to remove the sizing agent adhering to the glass fibers of the glass cloth; (4) Silane treatment process for surface treatment of degreased glass cloth using silane coupling agent; (5) The selvage treatment process that allows organic resin to adhere to and cure the silane-treated glass cloth. (6) A slitting process in which the selvage treatment section is cut along the winding direction.

[0041] (1) Warping process The warping process involves winding a specified number of glass fibers into bundles according to the weaving density. To suppress fuzzing and / or yarn breakage during warping, a secondary sizing agent with starch, PVA, or similar components can be used to protect the surface of the glass fibers.

[0042] (2) Weaving process The weaving process is the process of obtaining glass cloth (the raw material for glass cloth) by weaving the bundles obtained in the warping process into the weft yarns. There are no particular limitations on the weaving method, and examples include weaving methods based on air-jet looms, water-jet looms, rapier looms, shuttle looms, etc.

[0043] (3) Deoiling process The degreasing process can be performed by heating the aforementioned glass cloth raw material at 100°C to 1,500°C to remove the secondary sizing agent and its modifiers. The heating amount, expressed as the product of the heating temperature (°C) of 100°C or higher and the heating time (h), is preferably 450 (°C·h) or higher.

[0044] The heating furnace used for heating is preferably set to a vacuum or a dry atmosphere with a dew point below 15°C. If such a heating furnace is used, the heat release mechanism is not limited, and examples include gas furnaces, electric furnaces, muffle furnaces, and laser heating. Among these, electric furnaces, muffle furnaces, and laser heating are preferred.

[0045] There are no particular limitations on the heating method. Examples include intermittent heating in which the glass cloth is de-oiled directly in a heating furnace while it is in a wound state, and roller-to-roller heating with a winding and unwinding mechanism that de-oils the glass cloth while it is being transported.

[0046] (4) Silane treatment process A glass cloth with a surface treatment using a silane coupling agent is obtained through a silane treatment process. Specifically, as described below, the glass cloth is treated with a silane treatment solution containing a silane coupling agent.

[0047] Regarding the silane treatment solution for treating glass cloth, there are no particular limitations. From the viewpoint of productivity and environmental impact, an aqueous dispersion of 0.05% to 1% by mass of silane coupling agent is suitable. An aqueous dispersion can be prepared by adding a pH adjuster to the silane coupling agent. As for the pH adjuster, there are no particular limitations; it is preferable to adjust it using acetic acid and / or ammonia, depending on the silane coupling agent used. As for the silane treatment, there are no particular limitations; simply immerse the glass cloth to be treated with silane in the above-mentioned aqueous dispersion. The temperature and / or time can be appropriately selected from 50 to 200°C, 30 seconds to 1 hour, etc.

[0048] Examples of silane coupling agents include trimethylmethoxysilane, trimethylethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, trimethoxysilane, triethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenylmethylvinylethoxysilane, naphthyltrimethoxysilane, naphthyltriethoxysilane, 1,4-bis(methoxydimethylsilyl)benzene, tetramethoxysilane, and tetraethoxysilane. Silane, n-propyltriethoxysilane, hexyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-epoxypropoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, Hexyl)-ethylmethyldimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyldimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 3-methacryloyloxypropyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane Alkoxysilane compounds such as N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane and its hydrochloride, N-(vinylbenzyl)-2-aminoethyl-3-aminopropylmethyldimethoxysilane and its hydrochloride, 3-isocyanate propyltriethoxysilane, tri-(trimethoxysilylpropyl)isocyanurate, 3-ureopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, and bis(triethoxysilylpropyl)tetrasulfide can be used, either alone or in combination of two or more. Preferably, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane are preferred. The silane coupling agent is not limited to these; one can be used alone or in combination of two or more.

[0049] (5) Selvage treatment process The edge finishing process refers to the process of applying and curing an organic resin to prevent defects such as yarn breakage and weave structure problems during the cutting of glass cloth. There are no particular limitations on the organic resin; examples include thermosetting resins and UV-curing resins. To ensure a uniform and thin coating, a solvent can be used for dilution.

[0050] There are no particular limitations on the method of coating organic resins; any existing known method can be appropriately selected, such as roller coating, mold coating, spray coating, and curtain coating. From the viewpoint of minimizing the variation in coating width, roller coating and mold coating are preferred.

[0051] (6) Cutting process The slitting process involves cutting along the warp yarns in the winding direction at designated positions in the aforementioned selvage treatment section, removing portions from the two edges of the glass cloth up to the designated positions in the selvage treatment section.

[0052] Furthermore, for glass cloth, in order to improve resin impregnation in subsequent processes, fiber splitting treatment can usually be performed, for example, before the degreasing process or during the surface treatment process. There are no particular limitations on the fiber splitting treatment method, but examples include: fiber splitting methods using ultrasound, methods based on high-pressure columnar water flow, and methods using gas-liquid mixed mist with adjusted air-water volume ratios, depending on the type of glass cloth. The effects of the present invention can be obtained regardless of whether fiber splitting is performed.

[0053] The various steps in the above-described method for manufacturing glass cloth do not necessarily need to be performed as separate steps; multiple steps can be combined into one step. Furthermore, if possible, the order of the above steps can be appropriately changed. Example

[0054] The following examples and comparative examples illustrate the present invention, but the present invention is not limited to the following examples.

[0055] (Example 1) The warp yarn (1) is made of quartz glass fiber with a SiO2 content of 99.9% or more and a count of 4.8 g / km, and the warp yarn (2) is made of E glass fiber with a SiO2 content of 53% or more and a count of 4.8 g / km. The warp yarn (1) is 632.5 mm from the center of the width of the glass cloth, and the warp yarn (2) is located outside the width direction of the warp yarn (1). The weft yarn is made of quartz glass fiber with a SiO2 content of 99.9% or more and a count of 4.8 g / km. The IPC standard 1035 glass cloth is manufactured by using an electric furnace B80×85×200-3Z12-10 manufactured by NEMS. The temperature is raised to 400℃ at 100℃ / h and held for 24 hours, and then cooled at 30℃ / h. During this period, from the start of heating to the start of cooling, dry air with a dew point of -20°C, produced using HITACHI Inverter Package Oilfree Bebicon POD-15VNP, is introduced into the electric furnace every hour in a volume of 5 times for oil removal.

[0056] Next, the silane coupling treatment solution was prepared. Purified water with a conductivity of 15 MΩ·cm, produced using a Milli-QIX 7010 pure water production system manufactured by MERCK Corporation, was mixed with acetone (boiling point 56°C) manufactured by Tokyo Chemical Industry Co., Ltd. at a concentration of 20% by mass. Then, acetic acid manufactured by Tokyo Chemical Industry Co., Ltd., as a hydrolysis condensation catalyst, was added, and the mixture was stirred at 300 rpm at 25°C for 1 minute to prepare the mixture. Stirring continued under this condition, and 3-methacryloyloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Industry Co., Ltd., product name KBM-503), which had been pre-filtered using a DISMIC 13H membrane filter manufactured by ADVANTEC Corporation, was added at a concentration of 0.2% by mass relative to the aforementioned mixture over 1 minute. The final ratio was: acetone 20% by mass, acetic acid 0.1% by mass, KBM-503 0.20% by mass, and the remainder being purified water. The mixture was then stirred at 25°C for 1 hour.

[0057] The aforementioned silane coupling treatment solution was added to a silane treatment machine manufactured by Hirano Tecseed to impregnate the glass cloth. After removing excess treatment solution with a gap of 150 μm, it was dried at 110°C for 3 minutes to obtain silane-treated glass cloth. Next, using a slitting machine (LP11A-00K-001) manufactured by Shin-Etsu Engineering Co., Ltd., a weft treatment agent containing 100 parts by mass of tricyclodecanediethanol diacrylate (a difunctional acrylate) and 0.5 parts by mass of Omnirad 819 (manufactured by IGM, an α-hydroxyacetophenone compound) as a photopolymerization initiator was applied at a speed of 500 mJ / cm².2 The cumulative light intensity was irradiated by a 365nm ultraviolet LED. After curing the selvage treatment agent, 5mm was cut off from both ends to obtain glass cloth. The width T1 of the warp yarn (2) and the adhesion width R1 of the organic resin of the slit glass cloth are T1 / R1=0.5.

[0058] (Example 2) The warp yarn (2) was replaced with D glass fiber with a SiO2 composition of 72% by mass and a count of 4.8 g / km. Otherwise, the glass cloth was obtained in the same manner as in Example 1. The width T1 of the warp yarn (2) and the adhesion width R1 of the organic resin of the slit glass cloth were T1 / R1 = 0.5.

[0059] (Example 3) The warp yarn (2) was replaced with glass filament with a count of 2.8 g / km, and the glass cloth was otherwise obtained in the same manner as in Example 1. The width T1 of the warp yarn (2) and the adhesion width R1 of the organic resin of the slit glass cloth were T1 / R1 = 0.5.

[0060] (Comparative Example 1) The warp (1) is 627.5 mm from the center of the glass cloth width, and the warp (2) is the outer side of the width direction of the warp (1). Otherwise, the glass cloth is the same as in Example 1. The width T1 of the warp (2) of the cut glass cloth and the adhesion width R1 of the organic resin are T1 / R1=1.5.

[0061] (Comparative Example 2) The warp yarns (1) and (2) were replaced with quartz glass fibers with a SiO2 composition of 99.9% or more by mass and a count of 4.8 g / km. Otherwise, the glass cloth was obtained in the same manner as in Example 1.

[0062] The obtained glass cloth was evaluated as follows. The results are shown in Table 1.

[0063] [1] Dielectric loss tangent of glass cloth The dielectric loss tangent of the glass cloth at 10 GHz was measured using a cavity resonator (TE011 mode) manufactured by AET Corporation. It should be noted that the thickness of the glass cloth was measured using the theoretical film thickness, which is calculated according to the following formula. It should also be noted that the dielectric loss tangent measurement was performed on the portion without the attached organic resin. Theoretical film thickness t (μm) = weight per unit area (g / m²) 2 ) / Specific gravity (g / cm 3 ).

[0064] [2] Confirmation of whether there are cracks in the selvage during winding. When winding 2,000m of glass cloth into a paper tube with a diameter of 18cm, check whether cracks occur at the woven edge. 〇: The number of cracks on the edge of the fabric is less than 5 ×: The number of cracks on the edge of the fabric is more than 5.

[0065] [Table 1]

[0066] According to the results in Table 1, it is clear that if the glass cloth is the one of the present invention, the dielectric loss tangent is low, resulting in fewer cracks at the edge of the glass cloth that cause breakage, and the mass production performance is also excellent.

[0067] On the other hand, as in Comparative Example 1, when the width of the warp yarn with a SiO2 content of less than 90% is greater than the adhesion width of the organic resin, the dielectric loss tangent deteriorates. In addition, as in Comparative Example 2, in glass cloth composed only of quartz filaments with a SiO2 content of more than 90%, a large number of cracks occur at the selvage, and the glass cloth breaks during the manufacture of prepregs, resulting in poor productivity.

[0068] In this way, the glass cloth of the present invention satisfies the dielectric properties and mass production requirements of high-speed communication such as 5G, and has high utilization value in fields such as high-speed communication with the above requirements.

[0069] It should be noted that the present invention is not limited to the above-described embodiments. The above embodiments are illustrative examples, and any technical solutions having the same structure and achieving the same effect as those described in the claims of the present invention are included within the technical scope of the present invention.

[0070] Explanation of reference numerals in the attached figures 10. Fiberglass cloth 11. Area woven from warp yarns (1) 12. Area woven from warp yarns (2) 13 Areas with attached organic resin

Claims

1. A glass cloth, characterized in that, It is a glass cloth made of glass fibers as warp and weft yarns. The warp yarns consist of two types of glass fibers with different SiO2 compositions. The warp yarns (1) and (2) form at least one of the two edge portions in the width direction of the glass cloth. All edge portions woven from the warp yarns (2) are coated with organic resin. The width T1 woven from the warp yarns (2) and the width R1 coated with organic resin are T1 / R1≤1. The weft yarns are glass fibers with a SiO2 composition of 90% by mass or more. Warp yarn (1): Glass fiber with a SiO2 content of 90% or more by mass. Warp yarn (2): Glass fiber with a SiO2 content of more than 50% by mass and less than 90% by mass.

2. The glass cloth according to claim 1, characterized in that, The glass cloth is a glass cloth that has been surface-treated with a silane coupling agent, and the portion without the organic resin attached has a dielectric loss tangent of less than 0.0008 at 10 GHz.

Citation Information

Patent Citations

  • Annealed quartz glass cloth and manufacturing method thereof

    JP2021195689A

  • Glass composition for glass fibers, glass fibers, glass fiber fabric, and glass fiber-reinforced resin composition

    WO2021205698A1